Epistemologi Penafsiran Surah An-Nisa’ (4): 3 dalam Al-Qur’an: Studi Tafsir Abad Klasik dan Kontemporer - Wely Dozan (REVELATIA Jurnal Ilmu al-Qur`an dan Tafsir, 2025)
The interpretation of polygamy in Q.S. an-Nisa’ (4): 3 remains a contested discourse, driven by divergent epistemological and methodological frameworks between classical and contemporary scholars. This library research aims to trace the epistemological evolution of these interpretations and analyze the shifting paradigms across different eras by comparing classical commentaries, modern journals, and relevant literature. The findings reveal two primary trajectories: first, classical epistemology is heavily influenced by patriarchal culture and lacks gender-justice considerations, resulting in a textualist and subjective-patriarchal orientation. Second, contemporary epistemology emphasizes gender equality and social reality while rejecting patriarchal ideology, giving rise to a contextualist and objective-gender-neutral approach. This shift underscores that socio-cultural contexts and methodological frameworks significantly redefine the interpretation of polygamy within the Islamic intellectual tradition.